Época de colheita como modulador de compostos bioativos em cvs. de batata-doce minimamente processada - Silva, Valécia Nogueira Santos e (2019)
The harvest time of sweet potatoes is one of the important pre-harvest factors for modulating browning in minimally processed white sweet potatoes and whitening in colored fleshed ones. In this study, harvest times were evaluated for different white-fleshed sweet potato cultivars, Mãe de Família Roxa, BRS Cuia, BRS Rubissol and Petrolina, and colored-fleshed sweet potatoes, Beetroot (purple flesh), BRS Amélia and Jerimum ( orange pulp), which bring together different qualitative aspects for their commercialization after minimal processing. The roots were harvested at 120, 150 and 180 days after planting, subjected to minimal processing and maintained at 5 ° C for 10 days. The symptoms that led to the loss of visual quality for sweet potatoes were darkening and whitening, intensified in sweet potatoes harvested at 120 days. In the white pulp cultivars, harvested at 120 days, the activities of the enzymes PPO and POD were higher, being triggers for rapid browning. The colored pulp cultivars showed little darkening. There was a decrease in the contents of total phenolic compounds with the advance of the harvesting season, for all cultivars, except for cv. BRS Amélia. The delay in harvesting resulted in increments of total carotenoids on the first day for colored pulp cultivars, however, the content of total carotenoids decreased during conservation for these cultivars. The delay in harvesting from 120 to 180 days did not significantly increase the levels of starch, soluble solids and total soluble sugars. In addition, it was possible to suggest that cv. BRS Cuia is not suitable for minimal processing due to its quick browning after cutting and cv. Beets, due to their low sugar levels, were also not suitable for the fresh root industry, as is the case for minimally processed, but for the extraction industry of bioactive compounds, in which they have a prominent feature in their fabrics. For cv. Beet (purple) the content of betacyanin was higher in potatoes harvested at 120 days, however this content decreased during storage, unlike potatoes harvested at 150 and 180 days which showed a slight increase during storage, the content of betaxanthin maintained remained constant, in conservation, for potatoes harvested at 120 days and reduced for those harvested at 150 and 180 days. Sweet potatoes harvested between 150 and 180 days, under refrigerated conditions, showed higher industrial yield and darkened less during conservation, making these roots more attractive for consumption and allowing the producer to choose the time of harvest and cultivate in that time. according to market demand for sweet potatoes